The interpretation of code status concept among pediatric health care workers, a multicenter cross sectional study across Lebanon - Raymonda Chahrour; Amani Bannout; Marianne Majdalani; Rana Yamout; Ali Ismail; Elma Abou Raffoul; Jihane Moukhaiber (Frontiers in Medicine)
BackgroundCardiopulmonary resuscitation (CPR) use with no considerations given to patient selection or therapeutic aim resulted in extension of the agony, pain and dying process for terminally ill patients. Four Resuscitation-limiting Codes other than Full Code exist. In a conservative country like Lebanon, several factors can influence such decisions, namely the ethical, legal, religious perspectives, pediatric population, and more importantly the lack of protocol, healthcare workers (HCWs) knowledge, understanding and readiness to discuss terminal care with the parents. The objectives of the study are to evaluate the knowledge, behavior and comfort level of Lebanese pediatric HCWs in code status discussions, and to determine major obstacles encountered.MethodsThis is a cross-sectional observational study. An anonymous questionnaire has been sent electronically for 400 pediatric HCWs from different hospitals across Lebanon, over a period of 3 months.ResultsOf the 400 pediatric HCWs recruited, 235 completed the survey. 39.9% of medical doctors (MDs), and 62% of registered nurses (RNs) did not know about code status subtypes. Most of the MDs are using the paternalistic approach. There were significant differences between MDs and RNs regarding their point of view toward code status, but both thought that it was not defined in the Lebanese law (86.7% of MDs vs. 87% of RNs), and are not comfortable in such discussions (79% for MDs vs. 84.8% for RNs). The decisions taken by MDs regarding life-sustaining treatments (LSTs) in different resuscitation-limiting codes showed clearly the knowledge gap. Moreover, attendings and trainees differed significantly in their decisions, where the latter seemed more conservative. Pediatric HCWs in Lebanon are facing major obstacles when it comes to code status decisions.ConclusionCode status in Lebanon is an immature concept, and pediatric HCWs are challenged with conflicting decisions and obligations when it comes to code status discussions and LSTs. A multidisciplinary approach, with good communication between different members of the medical team would be the best. Addressing the obstacles encountered, and set a clear protocol will not only unify and solidify the HCWs decisions, but will have positive impact and repercussions on the patient care as well.